HUBUNGAN POWER OTOT TUNGKAI DENGAN HASIL LARI SPRINT 100 METER SISWA YANG MENGIKUTI EKSTRAKURIKULER ATLETIK SMP NEGERI 40 PEKANBARU - Jasmi yati; Ramadi Ramadi; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this research is to determine whether there is a correlation between leg muscle strength and 100-meter sprint results in students participating in atletic extracurricular activities at SMP Negeri 40 Pekanbaru. The objects of this research were 14 extracurricular athletic students at SMP Negeri 40 Pekanbaru, which were held in September 2019. Based on the results of research conducted by researchers and through a detailed and statistical data processing process, it was concluded that there was a correlation between leg muscle strength and sprint sprint results. 100 meters Students who take the Ateletic extracurricular at SMP Negeri 40 Pekanbaru, because r count is obtained = 0.895 and r table = α (0.05) = 0.553 where r count> r table so Ha can be accepted. There is a correlation between variable X and Y variables which this correlation has a very strong interpretation of the correlation with the interpretation of the value of r which can be seen from the results of the correlation analysis between leg muscle strength and the 100 meter sprint results. Key Words: Leg Muscle Power, 100 Meters